Prototype Smart Charging Untuk Sepeda Listrik Berbasis Internet of Things - Gillang Saputra; Ares Setiawan; Eko Sulistyo; Dora Palupi (Jurnal Inovasi Teknologi Terapan, 2026)
The increase in the use of electric bicycles has led to the need for an efficient and safe charging system. This study designed a prototype of a smart charging system for electric bicycles based on the Internet of Things (IoT) to facilitate real-time and remote monitoring of charging. This system uses an ESP32 microcontroller, a 24V 15A power supply, 400W and 1200W step-up converters, and ACS712 30A voltage and current sensors. Charging data is displayed through the Blynk application to facilitate user monitoring. Test results show that the voltage increases until it stabilizes, while the current decreases over time during charging, indicating that the system works safely and efficiently (voltage 45–57 V, current approximately 2 A to nearly 0 A, time 0 to 353 minutes). Electricity consumption increases at the start of charging and then decreases, while charging costs continue to accumulate, indicating that the system is capable of calculating energy and estimating costs in real-time (maximum energy approximately 0.0018 kWh, cost approximately Rp1,200–Rp1,300).